COMMUNICATION IN MASS COOPERATION AS A VUCA FACTOR IN MODERN SOCIO-ECONOMIC SHOCKS - Fedoniuk, Sergii (The Copernicus Journal of Political Studies, 2020)
Analyzing the prerequisites for the VUCA (Volatility, Uncertainty, Complexity, and Ambiguity) phenomenon – characteristic of the modern world, which is more variable and multilateral than before – the text discusses VUCA with regard to open cooperation in the context of socio-economic interactions. Instability, uncertainty, complexity, and ambiguity of the world are caused mainly by the expansion of the model of open (mass) cooperation between the participants of public communication. The system of global communication has transformed from a predominantly one-vector model with a targeted audience to an interactive mass system in which not only the specialized subjects of the communication process but also all participants reflect all the components of the VUCA concept. This combination of communicators has characteristics similar to a crowd formed under the influence of external provocation. The consequences of the impact of VUCA communication factors are spontaneous social and economic upheavals that have emerged with the rapid development of new technologies and communication models (North Africa and the Middle East in 2010–2011, Ukraine in 2013–2014). Over time, this trend has intensified, and the consequences are now manifested on a global scale (as in the case of socio-economic consequences of the 2020 COVID-19 pandemic). VUCA communication rests on the principles of mass cooperation, thus appropriate approaches and methods should be based on management in the VUCA world.